Menumbuhkan Jiwa Kewirausahaan Sejak Dini dengan Memotivasi dan Melatih Keterampilan untuk Siswa MTs Negeri 1 Yogyakarta - Anas Hidayat; Asmai Ishak; Albari Albari; Febriani Wahyusari Nurcahyanti; Budi Setiono (Department of Accounting, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
Community service is currently aimed at students at MTs Negeri 1 Yogyakarta, which aims to instill entrepreneurial insights, as well as foster and enhance an entrepreneurial spirit. Having an entrepreneurial spirit is an important point for the provision of students in the future. Apart from that, from this activity it is hoped that students can help the family economy and can also take advantage of their free time to carry out positive activities by way of entrepreneurship and minimize juvenile delinquency. This service activity was held on January 28, 2023 at the hall of MTs Negeri 1 Yogyakarta, with the title: